COVID-19 related mortality in older adults: analysis of the first wave in Colombia and Mexico - Mario Ulises Pérez-Zepeda; Santiago Campos-Fajardo; Carlos Cano-Gutierrez (Pan American Health Organization, 2021)
Objective. The aim of this study is to describe the mortality among older adults in the first wave of COVID-19 in Colombia and Mexico. Methods. This is an observational, prospective study on data obtained from open data sets that are publicly available on the websites of the health ministries of the respective countries. COVID-19 cases, age, sex, date to mortality, and mortality itself were analyzed with Kaplan-Meier curves and Cox regressions. Results. Data on 1 779 877 individuals were analyzed, 58.2% from Mexico, with a higher frequency of men for both countries, and 11.7% were older adults. Survival curves show a continuous increase in mortality for Mexico, with higher rates for older adults, while for Colombia the mortality was observed up to 50 days of the follow-up. Finally, hazard ratios were higher for older adults in both countries. Colombia implemented a rigid curfew for older adults, and the effect on mortality is clear from the survival curves. Conclusions. This finding shows the potential benefit that public policies could have on older adults.